1981
DOI: 10.1152/ajpgi.1981.241.1.g16
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic nervous control of migrating myoelectric complexes

Abstract: The role of intrinsic nerves in the control of migrating myoelectric complexes (MMCs) was studied in seven conscious dogs, each implanted with a set of eight bipolar Trimel wire electrodes. Local areas, 3-5 cm long, were perfused close intra-arterially via an exteriorized heparinized Silastic cannula. Experiments consisted of giving bolus injections of atropine (20-50 micrograms), hexamethonium (20 mg), and tetrodotoxin (TTX; 3-30 micrograms) via the catheter at varying periods of time with respect to the arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 0 publications
4
41
0
1
Order By: Relevance
“…Bioproducts, Walkersville, MD, U.S.A.) were used for smooth muscle cell dispersion techniques. 3 [H]QNB (Du Pont NEN, Boston, MA, U.S.A.) was used for muscarinic receptor binding studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioproducts, Walkersville, MD, U.S.A.) were used for smooth muscle cell dispersion techniques. 3 [H]QNB (Du Pont NEN, Boston, MA, U.S.A.) was used for muscarinic receptor binding studies.…”
Section: Methodsmentioning
confidence: 99%
“…Atropine (nonselective muscarinic antagonist), when administered intravenously or close-intra-arterially (arterial) completely blocks all spontaneous smooth muscle contractions in the gut (1)(2)(3). In the gastrointestinal system, muscarinic receptors play a significant role in coordination of peristalsis and propulsion of luminal contents (4).…”
mentioning
confidence: 99%
“…Nevertheless, in knockout mice lacking pacemaker ICCs, rhythmic contractions are still present (Spencer et al, 2003). In addition, the sodium channel blocker tetrodotoxin (TTX) abolishes gut motility, suggesting that initiation and propagation of MMCs mainly depend on neuronal activity (D'Antona et al, 2001;Sarna et al, 1981;Spencer et al, 2003). The importance of a functional enteric nervous system is further emphasised in conditions such as Hirschsprung's disease, where the absence of neurons in the distal part of the gastrointestinal tract causes severe constipation as result of impaired motility (Gershon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Small intestinal segments divided by transection and reanastomosed also generate their own MMC cycles independent of other segments [20,21]. It has been reported that bolus injection of atropine (anticholinergic antagonist), hexamethonium (ganglionic blocking agent), and tetrodotoxin (neuronal transmission blocking agent) via an intra-arterial catheter to the intestinal segment blocked phase 3 propagation at the perfused site [22]. Thus, these observations suggest that the initiation and propagation of the MMC are under intrinsic neural control, which is inherent to the enteric nervous system in the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%